Multiformalism techniques for critical infrastructure modelling. (28th September 2010) - Flammini, F.; Mazzocca, N.; Moscato, F.; Pappalardo, A.; Pragliola, C.; Vittorini, V.
This paper proposes an approach to use multiformalism techniques for critical infrastructure modelling. To this aim, the state of the art of related works on the subject is surveyed and a general scheme for intra and inter infrastructure models is described. Multiformalism approaches allow modellers to adapt the choice of formal languages to the nature, complexity and abstraction layer of the subsystems to be modelled. Another advantage is the possibility of reusing existing dependability models and solvers. Complexity and heterogeneity are managed through modularity, and composition allows for representing structural or functional dependencies. An example model based on a railway infrastructure is used to illustrate the concepts introduced by the paper.